A teacher-led classroom intervention in an area of Mexico experiencing community violence: A controlled mixed-method feasibility study - Suzanne M. Connolly; Leonor Zarazúa Menchaca; Héctor Figueroa Palafox; Heather L. Adams; John Freedom (PLoS ONE, 2025)
Objectives We aimed to explore the effectiveness of a daily ten-minute teacher-led group thought field therapy stress-reduction intervention on middle-school adolescents residing in an area experiencing high levels of interpersonal and community violence. We hypothesized that it would lead to a reduction of trauma symptoms and improve grades in reading and math. Methods In this double-masked feasibility study, adolescents in one school received a daily teacher-led thought field therapy intervention, and children in a different school served as an active waitlist group and received the same amount of time in a daily unguided drawing activity. The schools were geographically distant to prevent cross-contamination. Results Due to differences between groups in PTSD and academic performance prior to intervention, differences within each school’s scores over time were calculated and compared to each other for indirect assessment of effect. PTSD scores at the treatment school showed no lasting change at five months, while the control school showed moderate improvement. Adolescents in the treatment group demonstrated large improvements in both reading and math. Adolescents in the control group demonstrated moderate decrease in math, and no change in reading. Conclusions Preliminary evidence gained in this study suggests that a teacher-led ten-minute group thought field therapy exercise might assist adolescents’ learning in reading and math. However, in an area experiencing ongoing interpersonal and community violence, a more multicomponent approach with longer periods of intervention, caretaker involvement and individual therapy for those who might benefit from it, may be needed. Study registration number: ISRCTN10548974.